2005
DOI: 10.1126/science.1116894
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens Long-Term Depression and the Expression of Behavioral Sensitization

Abstract: Drug-dependent neural plasticity related to drug addiction and schizophrenia can be modeled in animals as behavioral sensitization, which is induced by repeated noncontingent or self-administration of many drugs of abuse. Molecular mechanisms that are critical for behavioral sensitization have yet to be specified. Long-term depression (LTD) of alpha-amino-3-hydroxy-5-methyl-isoxazole-4-propionic acid receptor (AMPAR)-mediated synaptic transmission in the brain has been proposed as a cellular substrate for lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
298
5
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 269 publications
(328 citation statements)
references
References 28 publications
16
298
5
2
Order By: Relevance
“…In the same aforementioned study, Ahmadian et al (2004) demonstrated that induction of LTD in hippocampal CA1 slices is associated with increased GluR2 tyrosine phosphorylation, and is prevented by postsynaptic application of the GluR2 3Y peptide. Likewise Brebner et al (2005) demonstrate that Tat-GluR2 3Y blocks the induction of LTD in nucleus accumbens neurons in an in vitro slice preparation. This is consistent with other studies that have implied a role for AMPA receptor endocytosis in mediating LTD (Wang and Linden, 2000;Xia et al, 2000).…”
Section: Blockade Of Ampa Receptor Endocytosis Does Not Effect the Acmentioning
confidence: 64%
See 4 more Smart Citations
“…In the same aforementioned study, Ahmadian et al (2004) demonstrated that induction of LTD in hippocampal CA1 slices is associated with increased GluR2 tyrosine phosphorylation, and is prevented by postsynaptic application of the GluR2 3Y peptide. Likewise Brebner et al (2005) demonstrate that Tat-GluR2 3Y blocks the induction of LTD in nucleus accumbens neurons in an in vitro slice preparation. This is consistent with other studies that have implied a role for AMPA receptor endocytosis in mediating LTD (Wang and Linden, 2000;Xia et al, 2000).…”
Section: Blockade Of Ampa Receptor Endocytosis Does Not Effect the Acmentioning
confidence: 64%
“…at a dose of 6 mg/kg 30 min before testing. Dose and route of administration for Tat-GluR2 3Y and Tat-GluR2 3S were chosen with reference to Brebner et al (2005). Dose and route of administration of Ro 25-6981 was chosen with reference to Fox et al (2006).…”
Section: Drugsmentioning
confidence: 99%
See 3 more Smart Citations